Pengaruh Inisiasi Menyusu Dini (IMD) Terhadap Lama Pelepasan Plasenta Pada Ibu Bersalin Kala III - Yona Sari; Sintha Sunarsih (LPPM STIKES Al-Ma'arif Baturaja, 2020)
According to UNICEF, as many as 30.000 babies who usually die in the first month of birth can be saved by initiating early breastfeeding. Early breastfeeding initiation is the process of allowing the baby to breastfeed itself immediately after birth. An important benefit of early breastfeeding initiation is that it can reduce maternal bleeding and speed up the placental release. Based on the Ministry of Health RI source (2013), the incidence of maternal bleeding is still very high, 30.3% of mothers die due to bleeding. Most cases of bleeding during the puerperium occur because placental retention of 16-17% incidence of placental retention causes bleeding cases. One way to prevent bleeding from placental retention is to initiate early breastfeeding. This study aims to determine the effect of early breastfeeding initiation on the length of placental release in maternity mothers at III. This research uses the True Experimental Design approach with Randomized Posttest Only Control Design. With the sampling taken by accidental sampling. Bivariate results showed the influence of early breastfeeding initiation on the length of placental release (ρ value = 0.003). The conclusions obtained in this study were that there was an effect of early breastfeeding initiation on the length of placental release in maternity mothers at III.